2019
DOI: 10.1055/s-0039-1677768
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-fetoprotein for Diagnosis, Prognosis, and Transplant Selection

Abstract: Reliable biomarkers are of great clinical value in predicting cancer occurrence/recurrence, anticipating its detection at an asymptomatic stage, supporting the radiological diagnosis, stratifying patients for prognosis and proper therapy, and measuring the response to treatment. Despite the plethora of biomarkers proposed for hepatocellular carcinoma (HCC), the first one identified, α-fetoprotein (AFP), remains the most utilized. This article reviews the lights and shadows of AFP as a surveillance test for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 154 publications
(226 reference statements)
3
51
0
1
Order By: Relevance
“…Serum AFP, however, is sometimes not entirely trustworthy, because AFP is often below the diagnostic value in some early‐stage or even a few late‐stage HCC cases . In contrast, AFP is elevated substantially in some patients with chronic hepatitis B (CHB), liver cirrhosis, and benign hepatic tumor diseases . Thus, AFP is a biomarker for reference only in the early diagnosis HCC without other supporting clinical information.…”
Section: Introductionmentioning
confidence: 99%
“…Serum AFP, however, is sometimes not entirely trustworthy, because AFP is often below the diagnostic value in some early‐stage or even a few late‐stage HCC cases . In contrast, AFP is elevated substantially in some patients with chronic hepatitis B (CHB), liver cirrhosis, and benign hepatic tumor diseases . Thus, AFP is a biomarker for reference only in the early diagnosis HCC without other supporting clinical information.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of alpha-fetoprotein (AFP), one of the two biomarkers suitable for large-scale screening in addition to the controversial prostate specific antigen [1]. AFP serum levels rapidly decrease after birth and remain below 10 ng mL −1 under healthy conditions except in pregnant women [2,3]. Since the expression of AFP is highly specific for the liver, it was found elevated in hepatocellular carcinoma (HCC) patients and proposed as a tumor biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…However, AFP alone is not enough for HCC diagnosis, screening or surveillance [4]. Its suboptimal performance, that is, increased levels in benign liver pathologies and teratomas or low levels in small HCC [5], has prompted that US and European guidelines allow HCC surveillance with or without AFP control, in contrast to Asian guidelines that recommend its use in combination with imaging techniques or even other biomarkers [2]. Nonetheless, it remains as a supplemental test when only low-quality or inconclusive images are available.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, AFP is the most widely used serum biomarker for HCC diagnosis. However, the diagnostic sensitivity of AFP is partially impacted by AFP− HCC 48 . Our study found that lnc85 was significantly increased in both AFP+ and AFP− HCC, and it distinguished AFP− HCC from HC and LC.…”
Section: Discussionmentioning
confidence: 59%